The Effectiveness of Mating Induction on Men’s Financial Risk-Taking: Relationship Experience Matters - Liu, Tingting; Wang, Zhuanzhuan; Zhu, Anrun; Zhang, Xi; Xing, Cai (Frontiers in Psychology, 2022)
Substantial evidence from experimental studies has shown that mating motivation increases men’s financial risk-taking behaviors. The present study proposed a new moderator, men’s past relationship experience, for this well-accepted link between mating motivation and financial risk-taking tendency. Heterosexual young men were randomly assigned to the mating condition and control condition, they completed a set of financial risk-taking tasks and reported their past relationship experience. A significant main effect of mating motivation and a significant interaction effect between experimental conditions (mating group, control group) and relationship experience emerged, suggesting that mating motivation increased financial risk-taking tendency only among men who have never been committed in a romantic relationship, rather than those who have had such experience. This moderating effect was replicated in two experiments. The present study contributed to the understanding of individual differences in the relationship between mating motivation and male financial risk-taking. The present findings also have important implications for financial industry and gambling companies to better target clients and advertise their high-risk products.